Archaeometric investigations of terra-cotta sarcophages from the excavations at einos (Enez) Turkey: An EDXRF Study - Kurap, Gülnur; Başaran, Sait; Uçar Çakan, Banu; Özsait Kocabaş, Işıl; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Asian Journal Of Chemistry, 11/100 Rajendra Nagar, Sector 3, Sahibabad 201 005, Ghaziabad, India, 2011)
In this study 11 clazomenian type sargophagi, found in ancient Ainos, one of the important archaeological site of Turkey, were investigated by EDXRF spectroscopy. The elemental composition of the painted parts and body samples of the sarcophagi were determined and the pigments used in the decorated parts were identified. Chemometric treatment of the XRF data was performed and principle component analysis revealed presence of 3 distinct groups.
Keywords: Ancient Terra-Cotta Sarcophagi; Archaeometry; Inorganic Pigments; XRF; EDXRF; Principle Component Analysis; Spectrophotometric Determination; Micro-Raman; Regression; Potteries; FT-IR; Antik Terra-Cotta Lahitler; Arkeometri; Inorganik Pigmentler; Temel Bileşen Analizi; Spektrofotometrik Tespit; Mikro-Raman; Gerileme; Çanak-Çömlek